Kinetic stabilisation of a molecular strontium hydride complex using an extremely bulky amidinate ligand. Issue 7 (8th January 2018) - de Bruin-Dickason, Caspar N.; Sutcliffe, Thomas; Alvarez Lamsfus, Carlos; Deacon, Glen B.; Maron, Laurent; Jones, Cameron
Abstract : The first dimeric strontium hydride complex (see picture, Dip = 2, 6-diisopropylphenyl, Ad = 1-adamantyl), and analogous magnesium hydride systems, have been kinetically stabilised by extremely bulky amidinate ligands, developed for this study. Abstract : Two extremely bulky amidinate ligands, [RC{N(Dip)}{N(Ar † )}] − (Dip = 2, 6-diisopropylphenyl; Ar † = C6 H2 {C(H)Ph2 }2 Pr i -2, 6, 4; R = 1-adamantyl (L Ad ), tert -butyl (L t Bu )) have been developed and utilised for the kinetic stabilisation of the strontium and magnesium hydride complexes, [L Ad Sr(μ-H)]2 and [L R Mg(μ-H)]2 (R = Ad or Bu t ). The former represents the missing link in the series of dimeric systems, [LAe(μ-H)]2 (Ae = alkaline earth metal). The structure and bonding of the complexes have been studied by crystallographic, spectroscopic and computational techniques.